2011
DOI: 10.1038/nrn3085
|View full text |Cite
|
Sign up to set email alerts
|

A pathophysiological framework of hippocampal dysfunction in ageing and disease

Abstract: The hippocampal formation has been implicated in a growing number of disorders, from Alzheimer's disease and cognitive ageing to schizophrenia and depression. How can the hippocampal formation, a complex circuit that spans the temporal lobes, be involved in a range of such phenotypically diverse and mechanistically distinct disorders? Recent neuroimaging findings indicate that these disorders differentially target distinct subregions of the hippocampal circuit. In addition, some disorders are associated with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
743
6
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 799 publications
(789 citation statements)
references
References 186 publications
29
743
6
11
Order By: Relevance
“…In line with a recent study that reported greater hippocampal shape alterations in patients with schizophrenia and prior comorbid alcohol use disorders (Smith et al, 2011), we hypothesised that cannabis use would exert an additional effect on the hippocampal pathology typically observed in schizophrenia, particularly in the anterior hippocampus (Csernansky et al, 2002;Small et al, 2011;Tamminga et al, 2010).…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…In line with a recent study that reported greater hippocampal shape alterations in patients with schizophrenia and prior comorbid alcohol use disorders (Smith et al, 2011), we hypothesised that cannabis use would exert an additional effect on the hippocampal pathology typically observed in schizophrenia, particularly in the anterior hippocampus (Csernansky et al, 2002;Small et al, 2011;Tamminga et al, 2010).…”
Section: Introductionsupporting
confidence: 64%
“…Hippocampal pathophysiology is evident in a diverse range of disorders that appear to differentially target distinct subregions of the hippocampus (Small et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this large variance is partly the differences in the ability to recruit additional brain areas for task solving, which can partially counterbalance the effect of functional decline [7]. Another factor, which may contribute to the differences in the effect of ageing on cognitive functions, is the large variance in the sensitivity to age-related changes between brain areas and neuronal types [8,9]. Nevertheless, it is generally assumed that age-related progression in synaptic dysfunction and neuronal plasticity impairment are the direct causes of the alterations in neuronal connectivity [10] and thus functional deficits in ageing [11].…”
Section: Functional Histological and Molecular Changes In The Ageingmentioning
confidence: 99%
“…Based on these results, it was concluded that lesions of the DG decrease the efficiency of spatial pattern separation, which results in impairments on trials with increased spatial proximity and increased spatial similarity among working memory representations. Holden, Hoebel, Loftis, and Gilbert (2012) used an analogous task to that used for rats (Gilbert et al, 2001) to test young participants compared to aged participants who are likely to have DG dysfunction (see Small, et al, 2011). They report that aged participants that do not perform well on standard memory tests are impaired in displaying a pattern separation function.…”
Section: Pattern Separation --Spatial Attributementioning
confidence: 99%